PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR DI BEI - Setiawan, Yudha Dwi Adi; Fitria, Astri (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
One of the important objectives of the establishment of a company is to improve the welfare of the owner or the stockholders, or maximizing the welfare of the stockholders by improving the performance of the company. The improvement of the performance of the company can be achieved if the company can operate by the achieving the determined profit. On the other hand, the manager as the administrator of the company has different objectives particularly in improving the individual achievement and the compensation which will be accepted. If the manager of the company conducts an action by ignoring the interests of investors then it will cause the collapse of the expectations of investors about returns of investment which has been invested by them. The samples are 24 manufacturing companies which have been selected by using purposive sampling which are listed in Indonesia Stock Exchange in 2010-2012 periods. The multiple linear regressions analysis method is used as the analysis technique. The result of this research describes that the research regressions model has met the classic assumption test which means that this regressions model is that the regression model is free from heteroscedasticity, multicolinearity, and autocorrelation, and the generated data has been distributed normally. The multiple linear regressions describes that the independent board of commissioners have significant influence to the performance of the company, the board of directors have significant influence to the performance of the company, the institutional ownership has significant influence to the performance of the company, the managerial ownership has significant and negative influence to performance of the company.Keywords: The Independent Board of Commisioners, the Size of the Board of Directors, The Institutional Ownership, The Managerial Ownership and the Performance of the Company.